Proposal for an Institutional Carpooling System among workers from the public-education sector - Rey-Merchán, María del Carmen (2022)
Car journeys to work represent a high percentage of daily mobility. Carpooling can be an efficient alternative for managing this transport demand. Carpooling benefits are not limited to reducing emissions and energy consumption: users can also benefit in the reduction in travel costs and travel time using high-occupancy vehicle lanes, as well as reducing commuting stress. The organization of such a system is not easy to carry out individually. Institutions and companies with a high number of employees are suitable for carpooling initiatives, and the education sector holds a high number of workers. Considering the large number of teachers and the fact that many of them are regular drivers, the sector presents an opportunity to design a formal carpooling transport system. This paper presents the design of a proposal for a carpooling system among workers from the education sector in the region of Andalusia, Spain. The system yielded relevant benefits such as cost savings, emissions reductions, and a high number of potential users. The designed system can potentially improve transport conditions for workers in commuting displacements and reduce occupational traffic accidents.